Nurses' patterns of knowing about HIV disclosure to children - Renata de Moura Bubadué; Ivone Evangelista Cabral; Franco Carnevale (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to identify and analyze nurses' patterns of knowing and experiences with the preparation of families for disclosure to children living with HIV seropositivity. Methods: thirteen pediatric nurses from Rio de Janeiro participated in the research using the sensitive creative method. Data were treated with Orlandi's discourse analysis and Carper's patterns of knowing. Results: nurses' speeches revealed socioculturally constructed imaginary and ideological formations. The personal pattern of knowing, under the influence of negative media about the disease in the 1980s, generated stigma and prejudice. Empirical, esthetic, and ethical patterns were built on training and professional practice of the 1990s-2010s. They composed a context of (in)security about competence, to contribute to preparing families to disclose HIV to children. Final Considerations: nurses' experience demonstrates knowledge to intervene and many challenges for their practical appropriation.